1993
DOI: 10.1115/1.2900734
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Nonlinear Dynamic Systems Using Neural Networks

Abstract: A procedure based on the use of artificial neural networks for the identification of nonlinear dynamic systems is developed and applied to the damped Duffing oscillator under deterministic excitation. The “generalization” ability of neural networks is invoked to predict the response of the same nonlinear oscillator under stochastic excitations of differing magnitude. The analogy between the neural network approach and a qualitatively similar nonparametric identification technique previously developed by the au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(66 citation statements)
references
References 6 publications
0
65
0
1
Order By: Relevance
“…Despite the many developments, nonparametric identification schemes can still be computationally expensive, depending on the type and scale of the system. As an example of the use of a ANN based scheme, we cite the work of Masri, Chassiakos, and Caughey (231) . They use a three-layered feed-forward neural network to model a damped Düffing oscillator.…”
Section: Journal Of System Design and Dynamicsmentioning
confidence: 99%
“…Despite the many developments, nonparametric identification schemes can still be computationally expensive, depending on the type and scale of the system. As an example of the use of a ANN based scheme, we cite the work of Masri, Chassiakos, and Caughey (231) . They use a three-layered feed-forward neural network to model a damped Düffing oscillator.…”
Section: Journal Of System Design and Dynamicsmentioning
confidence: 99%
“…These limitations make it di cult for non-parametric methods to be applied in on-line applications. Among the nonparametric identiÿcation schemes, the artiÿcial neural network approach has been recently used in characterizing structure-unknown non-linear systems [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In the engineering field, when ships or other floating bodies are subjected to large roll motions in waves, either when sailing or when at anchor, they experience nonlinear roll damping, which can be characterized as a type of velocitydependent damping of the form   f y  in eqn (1). This phenomenon is usually caused physically by the effects of nonlinear free-surface wave making and the nonlinear viscous dissipation of fluid flow.…”
Section: Motion Responsesmentioning
confidence: 99%
“…In the last two decades, there has been a lot of research work on the subject of dynamic system identification conducted by Masri et al [1], Chassiakos and Masri [2], Liang et al [3,4], Spina et al [5], Iourtchenko and Dimentberg [6], and others [7][8][9][10][11][12][13][14][15][16][17]. However, most of this research has identified the nonlinear characteristics of either damping or the restoring force.…”
Section: Introductionmentioning
confidence: 99%